A social attention with altmetric score analysis on the relationship between oxidative stress and cancer - Ferhat Hanikoglu; Gokay Vardar; Tomris Ozben; Mehmet Karadag; Mehmet Dokur (Medicine Science, 2022)
Oxidative stress has a crucial role in the development of various cancers. The aim of our study was to identify and analyze research articles about oxidative stress and cancer that have attracted the highest online attention. Our study is the first one evaluating social media attention to the articles on cancer and oxidative stress published in academic literature. Altmetric Explorer was used to identify research articles about oxidative stress and cancer. We evaluated the top 50 research articles having the highest Altmetric attention scores (AAS), using the Altmetric.com database. The Altmetric Attention Score (AAS) of 50 articles (T50) investigated was between 15 and 445 (mean±SD; 60.66±86.18). The social media platforms where the T50 articles are mentioned from highest to the lowest scores are the Facebook (n=2678) followed by Twitter (n=886) and Google + users (n=214). According to demographic breakdowns in Twitter, tweet counts were similar between scientists (34%) and not scientists (32%). Total citations of the 50 articles ranged from 3 to 3700 (mean ± SE; 203.40±87.07). A weak statistically significant positive correlation was found between the Altmetric score and the Q category (r=0.338: p=0.016). Interestingly, there was no correlation between Altmetric score and number of article citations. The increasing use of online social media platforms makes this area worthy, and the online impact of an article is becoming progressively more convenient for academic and public accessibility. Social media also may give oppurtunity to the researchers for disseminating their studies in scholar and non-scholar platforms. [Med-Science 2022; 11(2.000): 699-707]